Respuesta :

znk

Answer:

mn(x) = 5x³ + 9x² + 15x + 27

Step-by-step explanation:

mn(x) = m(x) × n(x)

mn(x) = (x² + 3)(5x + 9)

We can evaluate this expression by using the FOIL method.

First terms:    x² × 5x = 5x³

Outer terms: x² × 9    =        +9x²

Inner terms:  3 × 5x    =                 +15x

Last terms:   3 × 9      =                           +27

                       mn(x) = 5x³ + 9x² + 15x + 27

Answer:

A: 5[tex]x^{3}[/tex] + 9[tex]x^{2}[/tex] + 15x + 27

Step-by-step explanation:

ACCESS MORE